Tiroides lingual: reporte de dos casos - Duque-Serna, Francisco Levi; Londoño-Blair, Juan Luis; Orozco-Paredes, Benjamín (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The thyroid gland has an important function in the body due to its hormonal action in tissue and ceJ/ulargrowth. ripen and normal function. The thyroid anlage must migrate down ward duringembryogenesis to allow lusion 01 the lateralprominences of the tongue and, if these lails, it's trapped in tongue base. Two cases are reported in cbild's aged fourand eleven whopresented with a visiblemass in theposterior view of the tongue, diagnosed as a lingual thyroid, confírmed with Thyroid gammagraphy.